Peran Buruh Tani Perempuan Terhadap Ekonomi Keluarga Di Desa Atep Satu Kecamatan Langowan Selatan Kabupaten Minahasa - Silap, Brilian Naftaly; Laoh, Esry Olly Harryani; Maweikere, Audrey Julia Maria (Sam Ratulangi University, 2023)
The purpose of this study was to determine the role of women farm laborers on the family economy based on income contribution and work time in Atep Satu Village, Langowan Selatan Subdistrict, Minahasa Regency. This research was conducted for three months, from May to July 2022, starting from the preparation to the preparation of the research report. The method used in this research is the survey method by taking primary data and secondary data. Primary data was obtained through a list of questions that had been prepared, while secondary data was obtained from the sub-district office, village office, and related agencies. Sampling in this study used the method (simple random sampling) with the number of female farm laborers sampled as many as 30 out of 137 women who work as farm laborers and are married. The data obtained in this study were analyzed through the identification of the role of income, using the descriptive analysis method of the activities of the role of women farm workers in the household calculated based on the results of the work time. Based on the results of the study, the role of women farm laborers on the family economy in Atep Satu Village, Langowan Selatan Subdistrict, Minahasa Regency is the contribution of women farm laborers' income of 27.84% while the use of working time of women farm laborers is 23%. So in this case the highest contribution is 45.45% and the lowest is 18.82%.